Hybrid Aqueous/Nonaqueous Water‐in‐Bisalt Electrolyte Enables Safe Dual Ion Batteries. Issue 17 (29th March 2020) - Zhu, Jiaojiao; Xu, Yongtai; Fu, Yujun; Xiao, Dewei; Li, Yali; Liu, Lingyang; Wang, Yue; Zhang, Qingnuan; Li, Junshuai; Yan, Xingbin
Abstract: Dual ion batteries (DIBs) have recently attracted ever‐increasing attention owing to the potential advantages of low material cost and good environmental friendliness. However, the potential safety hazards, cost, and environmental concerns mainly resulted from the commonly used nonaqueous organic solvents severely hinder the practical application of DIBs. Herein, a hybrid aqueous/nonaqueous water‐in‐bisalt electrolyte with both broad electrochemical stability window and excellent safety performance is developed. The lithium‐based DIB assembled using KS6 graphite and niobium pentoxide as the active materials in the cathode and anode exhibits good comprehensive performance including capacity, cycling stability, rate performance, and medium discharge voltage. Initial capacities of ≈47.6 and 29.6 mAh g −1 retention after 300 cycles can be delivered with a medium discharge voltage of around 2.2 V in the voltage window of 0–3.2 V at the current density of 200 mA g −1 . Good rate performance for the battery can be indicated by 29.7 mAh g −1 discharge capacity retention at 400 mA g −1 . It is noteworthy that the coulombic efficiency of the battery can reach as high as 93.9%, which is comparable to that of the corresponding DIBs using nonaqueous organic electrolytes. Abstract : The lithium‐based dual ion battery assembled using hybrid aqueous/nonaqueous water‐in‐bisalt electrolyte exhibits both excellent safety performance and good comprehensive performance of capacity, cycling stability, medium discharge, and rate performance under the working voltage window of 0–3.2 V. It can light up a green light‐emitting diode (LED) with the nominal voltage of 3.0–3.2 V.